DIFFERENTIATION OF SOLID THYROID NODULES USING HIGH FREQUENCY ULTRASOUND AND CORRELATION WITH HISTOPATHOLOGY - Shama Aslam; Murtaza Ali; Nosheen Ahmad et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT: OBJECTIVE: Aim of my study is to determine the diagnostic accuracy of ultrasound (US) classiﬁcation system for diﬀerentiation of solid thyroid nodules whether they are benign or malignant. MATERIALS AND METHODS: We enrolled 191 patients who underwent real-time US neck and found to have solid thyroid nodules followed by ﬁne-needle aspiration cytology of nodules. Real time USG was used to classify thyroid nodules into 1 of 5 diagnostic categories: Malignant, suspicious for malignant lesion, borderline categories, probably benign lesions and benign categories. We found the diagnostic accuracy of thyroid nodules characteristics with the histopathological results. RESULTS: Out of the 96 solid thyroid nodules, 89 underwent thyroid surgery. According to US characteristics for these 96 nodules we categorize as malignant (n = 26), suspected for malignancy (n = 8), borderline lesion (n = 12), probably benign (n = 8), and benign (n = 41). We apply receiver-operating characteristic curve analysis which shows that when we use US for the diagnosis of solid thyroid nodules, as we use 5 categories of USG neck for US classiﬁcation system. The sensitivity 86%, speciﬁcity 95%, PPV 91%, NPV 92%, and found high diagnostic accuracy i.e. 92%, when benign, probably benign, and borderline categories were collectively classiﬁed as benign entity. CONCLUSION: The thyroid US having high diagnostic accuracy for solid thyroid nodules especially when we use the 5 category US classiﬁcation system.